The Diffuse Nature of the Academic Norm in “Libro de estilo de la lengua española” - Bustos Gisbert, José Manuel (2024)
This paper analyzes the way in which linguistic accuracy is formulated in El libro de estilo de la lengua española (2018), the latest normative publication by the Real Academia de la Lengua (Royal Spanish Academy) and the Asociación de Academias de la Lengua Española (Association of Academies of the Spanish Language). We show that more than half of the rules listed are of a diffuse, or fuzzy nature. We study three kinds of fuzzy rules: rules with a low deontic load, which have little prescriptive character; confusing rules, which are imprecise or subjective in nature; and rules for highly specific cases, with a very limited field of application. Finally, we note that it is not unusual for these three types to appear together.